(untitled) (MAUSAM, 1991)
Ozone soundings made from Dakshin Gangotri, Antarctica during 1987 are presented. The vertical distribution of ozone over Antarctica is characterised by a double peak profile, one around 200-150 hPa and the other around 50 hPa. During late winter-early spring the upper peak is considerably depleted. Tropospheric ozoe remains low and nearly constant throughout the year.